2021
DOI: 10.3389/fnut.2021.763809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Potential Mechanism of Maternal Micronutrient Intake on Offspring Glucose Metabolism: An Emerging Field

Abstract: Diabetes has become the most common metabolic disease around the world. In addition to genetic and environmental factors in adulthood, the early life environment is critical to the progression of diabetes in adults, especially the environment during the fetal period; this concept is called “fetal programming.” Substantial evidence has illustrated the key role of early life macronutrient in programming metabolic diseases. Recently, the effect of maternal micronutrient intake on offspring glucose metabolism duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 163 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…The availability of maternal nutrients has a direct impact on fetal growth. 1 Fuel sources have an important role in energy balance, as well as cellular and physiological processes. This may play a key role in regulating active food intake after conception in growing embryos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of maternal nutrients has a direct impact on fetal growth. 1 Fuel sources have an important role in energy balance, as well as cellular and physiological processes. This may play a key role in regulating active food intake after conception in growing embryos.…”
Section: Introductionmentioning
confidence: 99%
“…This may play a key role in regulating active food intake after conception in growing embryos. 1 , 2 Although all physiological processes necessitate energy during development, the thrifty hypothesis of developmental programming postulates that intrauterine exposure to unfavorable environments, such as excess nutrients, contributes to the pathophysiology of metabolic diseases later in life. 3 Energy fuel can be found in the form of sugar (glucose) and fat (triacylglycerides (TAGs)).…”
Section: Introductionmentioning
confidence: 99%
“…Third, previous research on offspring adiposity and prenatal diet has primarily focused on individual macronutrients 12 and micronutrients, 13 or pre-specified dietary quality indices, such as glycemic index 14 or the Mediterranean diet. 15 Data-driven techniques that identify naturally occurring diet patterns may offer a more comprehensive picture of prenatal diet.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, studies have demonstrated sex differences in measures of total body fat (i.e., BMI and body fat percentage), peripheral and central fat during the progression of puberty. 11 Third, previous research on offspring adiposity and prenatal diet has primarily focused on individual macronutrients 12 and micronutrients, 13 or pre-specified dietary quality indices, such as glycemic index 14 or the Mediterranean diet. 15 Data-driven techniques that identify naturally occurring diet patterns may offer a more comprehensive picture of prenatal diet.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nutrition could be considered as a major factor in the intrauterine environment, and this is known as fetal programming [ 4 ]. Furthermore, it has been established that maternal nutrition during different stages of pregnancy can induce permanent changes in the metabolism of the future offspring [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%